Historical Path Dependency and Media Freedom: Poland and Ukraine in the 1990s - Soroka, Svitlana; Palagnyuk, Yuliana (Studia Warmińskie, 2020)
The paper’s objective is to explain the different levels of media freedom in the post-socialist counties of Central and Eastern Europe in the 1990s, particularly in Poland and Ukraine. Even though these two countries are very close geographically, they started the process of transition from communism to democracy and initiated media reforms in the same period, in 10 years the results of these processes were different: Poland achieved the level of free media whereas Ukraine did not. The theories of Putnam’s deep long-term historical path dependence approach, East Central European historians and path dependence approaches of the economic reforms in the 1990s in the Central and Eastern European countries of post-socialist transitions are combined and applied for the analysis of media freedom in the 1990s and its deep historical predecessors in the sample countries.